HOAX AND THE CRISIS OF HEALTH COMMUNICATION-PUBLIC SPHERE - Praptiningsih, Winanti; Kurnia, Novi (Journal Communication Spectrum : Capturing New Perspectives in Communication, 2020)
Digital media development makes easier for everyone to share information. One of the visible characteristics is the change of audience role to be more active in the convergence era. At this point, hoax comes, such as vaccine danger which massively spreads in 2017-2018. The hoax case content is about kinds of concern, such as health clinical sense, work of digital media, to religious dogma. The article studies the vaccine danger polemic in 2017-2018, from the kinds of hoax appearance to the crisis of the health communication-public sphere in the digital era. This study finds that:  First, new media offers people more personal communication space where they can be a consumer and producer of information at once. Second, a clinical sense of health becomes a claim for being right that makes people trust scientific logic and eliminate critical attitude to manipulative works.  Third, the health information gap and lack of people's understanding of medical and technical terms make them active consumers who look for information independently through digital media.  Fourth, people concern about health information needs so they pay attention to see, read, and even share information. Fifth, hoax with certain interest tends to purpose on fake news that spreads in social media massively. Sixth, insufficient digital literacy in society makes them lost in mass information in the new media era. To cite this article (7th APA style): Praptiningsih, W. & Kurnia, N. (2020). Hoax and the Crisis of Communication-Public Sphere. Journal Communication Spectrum, 10(1), 1-9. http://doi.org/10.36782/jcs.v10i1.2002